Laminate and method for manufacturing laminate

By forming a metal layer including a seed layer, a barrier layer and a top layer on the silicon substrate and applying a thermal conductivity composition thereon, the problem that thermal conductivity, adhesion and refluxability in the prior art are difficult to achieve simultaneously, and efficient thermal conductivity and adhesion effects are achieved.

JP2025056444APending Publication Date: 2025-04-08DEXERIALS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023165919
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the prior art, when connecting the back electrode of the power device to the thermal 싱크 through the flux layer, it is difficult to achieve excellent thermal conductivity, adhesion and refluxability simultaneously.

Method used

A metal layer structure is adopted that includes a seed layer, a barrier layer and a top layer, which contains Ti, W, Al, Mo or Cr, the barrier layer comprises Ni, Al, Mo, Nb, TiN, TaN or WN, the top layer comprises Ag, Au, Cu, Pd or Pt, and a thermally conductive composition comprising curing components, hardeners, thermally conductive particles and low melting point metal particles are applied thereon, and a thermally conductive layer is formed by a heating step.

Benefits of technology

The contact resistance to the silicon substrate is reduced, and it has excellent thermal conductivity, adhesion and refluxability, and the thermal conductivity reaches 30 W/(m·K) or higher.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025056444000001_ABST
    Figure 2025056444000001_ABST
Patent Text Reader

Abstract

To provide a laminate which reduces contact resistance to a silicon substrate and can achieve excellent thermal conductivity, adhesiveness, and reflow resistance.SOLUTION: The laminate includes: a silicon substrate; a metal layer provided on the silicon substrate; and a thermally conductive layer provided on the metal layer and containing a curable component, a curing agent, a metal filler, and a low melting point metal. The metal layer has a seed layer containing at least one of Ti, W, Al, Mo and Cr.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate and a method for producing the laminate. [Background technology]

[0002] In large scale integration (LSI) and the like in various electronic devices, if the LSI itself is exposed to high temperatures for a long period of time due to heat generation from the elements used, this may lead to malfunction or failure. For this reason, thermally conductive materials are widely used to prevent the temperature of LSIs and the like from rising. The thermally conductive materials can prevent the temperature of the equipment from rising by diffusing the heat generated by the elements or by transmitting it to a heat dissipation member for dissipation outside the system, such as the atmosphere.

[0003] For example, it has been reported that a laminated film of Ti / Ni / Au serving as a back electrode of a power device is bonded to a heat sink via a solder layer (see, for example, Non-Patent Document 1). [Prior art documents] [Non-patent literature]

[0004] DENSO Technical Review Vol.11, No.2, pp108-114(2006) Summary of the Invention [Problem to be solved by the invention]

[0005] However, in the conventional technology described in Non-Patent Document 1, when the rear electrode of the power device is joined to a heat sink via solder, although thermal conductivity is obtained, there is a problem in that it is difficult to achieve excellent adhesion and reflow resistance.

[0006] The present invention aims to solve the above-mentioned problems in the prior art and to achieve the following objectives: That is, the present invention aims to provide a laminate that can reduce contact resistance with a silicon substrate and achieve excellent thermal conductivity, adhesion, and reflow resistance. [Means for solving the problem]

[0007] The means for solving the above problems are as follows. <1> A silicon substrate; a metal layer provided on the silicon substrate; a heat conductive layer provided on the metal layer, the heat conductive layer including a hardening component, a hardening agent, heat conductive particles, and a low melting point metal; The laminate is characterized in that the metal layer has a seed layer containing at least one of Ti, W, Al, Mo, and Cr. <2> The metal layer has, in order from the silicon substrate side, the seed layer and a barrier layer containing at least one of Ni, Al, Mo, Nb, TiN, TaN, and WN. <1> 1. The laminate according to claim 1 . <3> The metal layer has, in order from the silicon substrate side, the seed layer, the barrier layer, and a top layer containing at least one of Ag, Au, Cu, Pd, and Pt. <2> 1. The laminate according to claim 1 . <4> The thermal conductivity is 30W / (m K) or more. <1> from <3> The laminate according to any one of claims 1 to 5, <5> forming a metal layer having a seed layer containing at least one of Ti, W, Al, Mo, and Cr on a silicon substrate; applying a thermally conductive composition onto the metal layer, the thermally conductive composition including a curing component, a curing agent, thermally conductive particles, and low melting point metal particles; and heating the applied thermally conductive composition. <6> The metal layer has, in order from the silicon substrate side, the seed layer and a barrier layer containing at least one of Ni, Al, Mo, Nb, TiN, TaN, and WN. <5> 2. A method for producing the laminate according to claim 1 . <7> The metal layer has, in order from the silicon substrate side, the seed layer, the barrier layer, and a top layer containing at least one of Ag, Au, Cu, Pd, and Pt. <6> 2. A method for producing the laminate according to claim 1 . <8> The method according to claim 1, wherein the metal layer is formed by sputtering. <5> from <7> 13. A method for producing the laminate according to claim 12. Effect of the Invention

[0008] According to the present invention, it is possible to solve the above-mentioned problems in the conventional art, achieve the above-mentioned object, and provide a laminate that can reduce contact resistance with a silicon substrate and achieve excellent thermal conductivity, adhesion, and reflow resistance. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic diagram showing an example of a process for producing a laminate according to this embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a laminate according to this embodiment. [Diagram 3] FIG. 3 is a schematic diagram showing another example of the laminate according to the present embodiment. [Figure 4] FIG. 4 is a schematic diagram showing another example of the laminate according to the present embodiment. [Diagram 5] FIG. 5 is a schematic diagram showing another example of the laminate according to the present embodiment. [Figure 6] FIG. 6 is a schematic cross-sectional view showing an example of a heat dissipation structure having the laminate of this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] (Laminate) The laminate of the present invention comprises a silicon substrate, a metal layer, and a heat conductive layer, and may further comprise an opposing substrate and other members as required.

[0011] The metal layer has at least a seed layer, and preferably further has a barrier layer, and more preferably further has a top layer. The thermally conductive layer contains a curing component, a curing agent, thermally conductive particles, and a low-melting point metal, and further contains other components as required. Here, the low melting point metal refers to low melting point metal particles, which will be described later, and low melting point metal formed by melting and solidifying the low melting point metal particles.

[0012] The laminate of the present embodiment can reduce the contact resistance with the silicon substrate and achieve excellent thermal conductivity, adhesion, and reflow resistance. The laminate can achieve a thermal conductivity of 20 W / (m K) or more, preferably 25 W / (m K) or more, and more preferably 30 W / (m K) or more.

[0013] <Silicon substrate> The shape, structure, size, material, etc. of the silicon substrate are not particularly limited and can be appropriately selected depending on the purpose. Examples of the shape of the substrate include a plate shape, a sheet shape, etc. Examples of the structure of the substrate include a single-layer structure, a laminated structure, etc. The size of the substrate can be appropriately selected depending on the application, etc.

[0014] The average thickness of the silicon substrate is not particularly limited and can be appropriately selected depending on the purpose. The silicon base material may be the heat generating body (electronic component) itself in the heat dissipation structure.

[0015] <Metal layer> The metal layer is preferably formed on and in contact with the silicon substrate. The metal layer comprises at least a seed layer, and preferably further comprises a barrier layer, and preferably further comprises a top layer. Specifically, the metal layer may be a seed layer, a layer in which a seed layer and a barrier layer are laminated in this order from the silicon substrate side, a layered body in which a seed layer, a barrier layer and a top layer are laminated, or a layer in which a seed layer and a top layer are laminated. Any of these modes can be appropriately selected depending on the purpose.

[0016] The average thickness of the metal layer is not particularly limited and may be appropriately selected depending on the purpose, but is preferably 0.1 μm or more and 5 μm or less, and more preferably 0.2 μm or more and 2 μm or less.

[0017] <<Seed layer>> The seed layer contains at least one of Ti, W, Al, Mo, and Cr, and these may be used alone or in combination of two or more kinds. Among these, Ti, W and the like are preferred from the viewpoints of adhesion to the silicon substrate, hardness and thermal conductivity, and Ti is more preferred. The seed layer may be a single layer of a single metal or alloy, or may be a laminate thereof. The seed layer may also contain a metal silicide of silicon in the silicon substrate and at least one of Ti, W, Al, Mo, and Cr. By containing the metal silicide, adhesion to the silicon substrate is improved, and contact resistance with the silicon substrate is reduced, which is preferable.

[0018] The average thickness of the seed layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.05 μm or more and 0.5 μm or less, and more preferably 0.1 μm or more and 0.2 μm or less.

[0019] <<Barrier layer>> The barrier layer contains at least one of Ni, Al, Mo, Nb, TiN, TaN, and WN, and these may be used alone or in combination of two or more. Among these, Ni, Nb, etc. are preferred from the viewpoints of adhesion to the heat conductive layer, hardness, and thermal conductivity, and Ni is more preferred. The barrier layer may be a single layer of a single metal or alloy, or a laminate thereof.

[0020] The average thickness of the metal layer is not particularly limited and may be appropriately selected depending on the purpose, but is preferably 0.05 μm or more and 0.5 μm or less, and more preferably 0.1 μm or more and 0.3 μm or less.

[0021] <<Top Layer>> The top layer contains at least one of Ag, Au, Cu, Pd, and Pt, and these may be used alone or in combination of two or more kinds. Among these, Ag, Au and the like are preferred from the viewpoints of adhesion to the thermally conductive layer, the antioxidant effect of the barrier layer, hardness, and thermal conductivity, and Au is more preferred. The top layer may be a single layer of a single metal or alloy, or may be a laminate thereof.

[0022] The average thickness of the metal layer is not particularly limited and may be appropriately selected depending on the purpose, but is preferably 0.1 μm or more and 2 μm or less, and more preferably 0.2 μm or more and 1 μm or less.

[0023] <Thermal Conduction Layer> The heat conductive layer contains a curing component, a curing agent, heat conductive particles, and low melting point metal particles, and preferably contains a specific polymer, and further contains other components as necessary.

[0024] <<Curing component>> The curing component preferably contains at least one of an oxetane compound and an epoxy resin, and more preferably contains an oxetane compound and an epoxy resin.

[0025] -Oxirane ring compounds- The oxirane ring compound is a compound having an oxirane ring, and examples thereof include epoxy resins. The epoxy resin is not particularly limited and can be appropriately selected depending on the purpose. Examples of the epoxy resin include glycidyl ether type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A type epoxy resins, trisphenol type epoxy resins, tetraphenol type epoxy resins, phenol-xylylene type epoxy resins, naphthol-xylylene type epoxy resins, phenol-naphthol type epoxy resins, phenol-dicyclopentadiene type epoxy resins, alicyclic epoxy resins, and aliphatic epoxy resins. These may be used alone or in combination of two or more.

[0026] -Oxetane compounds- The oxetane compound is a compound having an oxetanyl group, and may be an aliphatic compound, an alicyclic compound, or an aromatic compound. The oxetane compound may be a monofunctional oxetane compound having only one oxetanyl group, or a polyfunctional oxetane compound having two or more oxetanyl groups.

[0027] The oxetane compound is not particularly limited and can be appropriately selected depending on the purpose. Examples of the oxetane compound include 3,7-bis(3-oxetanyl)-5-oxa-nonane, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, 1,2-bis[(3-ethyl-3-oxetanylmethoxy)methyl]ethane, 1,3-bis[(3-ethyl-3-oxetanylmethoxy)methyl]propane, ethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, triethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, tetraethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, 1,4-bis(3-ethyl-3-oxetanylmeth- oxy)butane, 1,6-bis(3-ethyl-3-oxetanylmethoxy)hexane, 3-ethyl-3-(phenoxy)methyloxetane, 3-ethyl-3-(cyclohexyloxymethyl)oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-(chloromethyl)oxetane, 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, xylylene bisoxetane, 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (OXBP), isophthalic acid bis[(3-ethyl-3-oxetanyl)methyl]ester (OXIPA), and the like. These may be used alone or in combination of two or more.

[0028] As the oxetane compound, commercially available products can be used. Examples of the commercially available products include the "ARON OXETANE (registered trademark)" series sold by Toagosei Co., Ltd. and the "ETERNACOLL (registered trademark)" series sold by Ube Industries, Ltd.

[0029] Among the oxirane ring compounds and oxetane compounds, glycidyl ether type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, phenol-dicyclopentadiene type epoxy resins, bisphenol A type epoxy resins, aliphatic epoxy resins, 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (OXBP), and isophthalic acid bis[(3-ethyl-3-oxetanyl)methyl]ester (OXIPA) are preferred.

[0030] <<Hardening agent>> The curing agent is a curing agent corresponding to the curing component, and examples thereof include polyaddition type curing agents such as polyfunctional carboxylic acid, acid anhydride type curing agent, aliphatic amine type curing agent, aromatic amine type curing agent (e.g., imidazole type curing agent), phenol type curing agent, and mercaptan type curing agent, and catalyst type curing agent such as imidazole. These may be used alone or in combination of two or more.

[0031] Among these, polyfunctional carboxylic acids are preferred, and polyfunctional carboxylic acids represented by at least one of the following general formula (I) and general formula (II) are more preferred.

[0032] [ka] In the above general formula (I), R 1 ~R 3 R each independently represents a hydrogen atom, an alkyl group, or a caprolactone skeleton. 4 R represents a hydrogen atom or an alkyl group which may be substituted with a hydroxyl group. 5 represents an alkyl group having 1 to 3 carbon atoms or an alkenyl group having 2 to 3 carbon atoms.

[0033] [ka] In the above general formula (II), R 1 and R 2R each independently represents a hydrogen atom, an alkyl group, or a caprolactone skeleton. 4 and R 6 R each independently represents a hydrogen atom or an alkyl group which may be substituted with a hydroxyl group. 5 represents an alkyl group having 1 to 3 carbon atoms or an alkenyl group having 2 to 3 carbon atoms.

[0034] R in the above general formula (I) 1 ~R 3 and R of general formula (II) 1 and R 2 In the formula, the alkyl group is preferably an alkyl group having 1 to 10 carbon atoms, and examples thereof include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a hexyl group, a heptyl group, an octyl group, a 2-ethylhexyl group, a tert-octyl group, and a cyclohexyl group. R in the above general formula (I) 1 ~R 3 and R of general formula (II) 1 and R 2 The caprolactone skeleton in the above formula (i) is represented by the following formula (i).

[0035] [ka] In the general formula (i), n represents an integer of 1 or more, and preferably an integer of 1 to 10. m represents an integer of 2 or more, and preferably an integer of 2 to 5.

[0036] R 4 and R 6 Examples of the alkyl group which may be substituted with a hydroxyl group in the above formula include a methyl group, an ethyl group, a propyl group, a -(CH 2 )-OH, -(CH 2 ) 2 -OH, -(CH 2 ) 3 -OH, etc.

[0037] R 5 Examples of the alkyl group having 1 to 3 carbon atoms include a methyl group, an ethyl group, a propyl group, and an isopropyl group. R5 Examples of the alkenyl group having 2 to 3 carbon atoms include a vinyl group, a 1-propenyl group, and an allyl group (2-propenyl group). R 5 is preferably either an alkyl group having 2 to 3 carbon atoms or an alkenyl group having 2 carbon atoms, in that it combines excellent flux activity and curability.

[0038] The polyfunctional carboxylic acid represented by at least one of the general formula (I) and the general formula (II) can be synthesized by reacting a specific acid anhydride with a specific polyfunctional alcohol, as described below.

[0039] [Method of producing polyfunctional carboxylic acid] The method for producing the polyfunctional carboxylic acid includes a step of esterifying an acid anhydride with a polyfunctional alcohol, and further includes other steps as necessary. The esterification reaction between the acid anhydride and the polyfunctional alcohol is not particularly limited and can be appropriately selected depending on the purpose.

[0040] Examples of the acid anhydride include succinic anhydride, glutaric anhydride, maleic anhydride, phthalic anhydride, benzoic anhydride, oxalic anhydride, etc. These may be used alone or in combination of two or more. Among these, succinic anhydride, glutaric anhydride, and maleic anhydride are preferred.

[0041] The polyfunctional alcohol is preferably difunctional or more, more preferably difunctional or more and tetrafunctional or less. Examples of the polyfunctional alcohol include caprolactone derivatives, glycerin, ethylene glycol, and propylene glycol. These may be used alone or in combination of two or more. Of these, caprolactone derivatives and glycerin are preferred.

[0042] The caprolactone derivatives include compounds having a caprolactone skeleton represented by the general formula (i) above. As the caprolactone derivative, commercially available products can be used, and examples of the commercially available products include PLACCEL 205, PLACCEL 205U, PLACCEL 303, and PLACCEL 410 (all manufactured by Daicel Corporation).

[0043] An example of an esterification reaction between a specific acid anhydride and a trifunctional alcohol is shown below. [ka] In the above reaction scheme, R 1 ~R 3 R represents a hydrogen atom, an alkyl group, or a caprolactone skeleton. 4 R represents a hydrogen atom or an alkyl group which may be substituted with a hydroxyl group. 5 represents an alkyl group having 1 to 3 carbon atoms or an alkenyl group having 2 to 3 carbon atoms.

[0044] The other steps are not particularly limited and can be appropriately selected depending on the purpose. For example, a concentration step, a separation and purification step, etc. can be mentioned.

[0045] The polyfunctional carboxylic acid represented by at least one of the general formulas (I) and (II) can achieve both a good flux effect and a good function as a curing agent. That is, the polyfunctional carboxylic acid represented by at least one of the general formulas (I) and (II) is liquid from room temperature to high temperature, and does not react during film formation, so that it can improve the wettability of the coating liquid. When heated in stages, it exerts the effect of a flux by the first heating stage, and then has a heat curing start switch function that starts curing by the curing components that were mixed together by the second heating stage. The heating temperature in the first stage is preferably 120°C to 150°C, for example. The heating temperature in the second stage is preferably 150°C to 190°C, for example.

[0046] The polyfunctional carboxylic acid is preferably liquid at 25°C and 150°C. Here, being liquid means having fluidity that allows application. The fact that the polyfunctional carboxylic acid is liquid at 25° C. and 150° C. can be confirmed, for example, by visually confirming the fluidity at 25° C. (room temperature) and by the presence or absence of an absorption peak up to 150° C. by DSC. The molecular weight of the polyfunctional carboxylic acid is preferably 800 g / mol or less, more preferably 400 g / mol or more and 700 g / mol or less, in view of being liquid. The molecular weight of the polyfunctional carboxylic acid can be measured, for example, by Shodex (registered trademark) GPC-101 (a product of Showa Denko K.K.).

[0047] The polyfunctional carboxylic acid is a curing agent having flux activity. By the heating in the first stage, the polyfunctional carboxylic acid has flux activity, and therefore the wettability of the molten low-melting point metal to the thermally conductive particles contained in the thermally conductive composition can be improved. Then, by heating in a second stage, the polyfunctional carboxylic acid can cure the curing component in the heat conductive layer.

[0048] The acid anhydride-based curing agent is preferred in that, when the curing component is an epoxy resin, no gas is generated during thermal curing, a long pot life can be achieved when mixed with the epoxy resin, and a good balance can be achieved between the electrical properties, chemical properties, and mechanical properties of the resulting cured product. Examples of the acid anhydride curing agent include cyclohexane-1,2-dicarboxylic anhydride, monoacid anhydrides of tricarboxylic acids, etc. Examples of the monoacid anhydrides of tricarboxylic acids include cyclohexane-1,2,4-tricarboxylic-1,2-acid anhydride, etc.

[0049] The curing agent preferably has flux activity from the viewpoint of improving the wettability of the molten low-melting point metal particles to the thermally conductive particles. Examples of methods for making the curing agent exhibit flux activity include methods of introducing protonic acid groups such as carboxyl groups, sulfonyl groups, and phosphoric acid groups into the curing agent by known methods. Among these, it is preferable to introduce a carboxyl group from the viewpoint of reactivity with the epoxy resin or oxetane compound as the curing component, and examples thereof include polycarboxylic acids containing a carboxyl group such as glutaric acid and succinic acid. The curing agent may also be glutaric anhydride or a compound modified from succinic anhydride, or a metal salt of a polycarboxylic acid such as silver glutarate.

[0050] <<Thermal conductive particles>> The thermally conductive particles are preferably at least any one of copper particles, silver-coated particles, and silver particles, and more preferably silver-coated particles. Examples of the silver-coated particles include silver-coated copper particles, silver-coated nickel particles, and silver-coated aluminum particles. The shape of the thermally conductive particles is not particularly limited and may be appropriately selected depending on the purpose. Examples of the shape include spherical, flat, granular, and acicular shapes.

[0051] The thermally conductive particles preferably have a volume average particle size of 1 μm to 100 μm, more preferably 5 μm to 70 μm, and even more preferably 5 μm to 50 μm. When the thermally conductive particles have a volume average particle size of 1 μm to 100 μm, excellent thermal conductivity can be achieved. The volume average particle size of the thermally conductive particles can be measured by a laser diffraction / scattering type particle size distribution measuring device (for example, Microtrac MT3300EXII, Microtrac Bell Corporation).

[0052] <<Low melting point metal>> The low melting point metal means the low melting point metal particles and the low melting point metal formed by melting and solidifying the low melting point metal particles. As the low melting point metal particles, solder particles as specified in JIS Z3282-1999 are preferably used.

[0053] Examples of the solder particles include Sn-Pb solder particles, Pb-Sn-Sb solder particles, Sn-Sb solder particles, Sn-Pb-Bi solder particles, Sn-Bi solder particles, Sn-Bi-Ag solder particles, Sn-Cu solder particles, Sn-Pb-Cu solder particles, Sn-In solder particles, Sn-Ag solder particles, Sn-Pb-Ag solder particles, Pb-Ag solder particles, Sn-Ag-Cu solder particles, etc. These may be used alone or in combination of two or more. Among these, solder particles containing Sn and at least one selected from Bi, Ag, Cu, and In are preferred, Sn-Bi based solder particles, Sn-Bi-Ag based solder particles, Sn-Ag-Cu based solder particles, and Sn-In based solder particles are more preferred, and Sn-Bi based solder particles containing Sn and Bi are even more preferred.

[0054] The shape of the low melting point metal particles is not particularly limited and may be appropriately selected depending on the purpose. Examples of the shape include spherical, flat, granular, and acicular shapes. The melting point of the low-melting-point metal particles is preferably 100°C or higher and 250°C or lower, and more preferably 120°C or higher and 200°C or lower.

[0055] The melting point of the low-melting-point metal particles is preferably lower than the heating temperature in the heating step in the method for producing a laminate of this embodiment, which will be described later. This allows the formation of a thermally conductive layer in which a network (continuous metal phase) is formed by the molten low-melting-point metal via the thermally conductive particles during hardening of the thermally conductive composition, thus realizing a laminate with excellent heat resistance, thermal conductivity, and adhesiveness.

[0056] The volume average particle diameter of the low-melting-point metal particles is preferably 10 μm or less, more preferably 1 μm or more and 7 μm or less. When the volume average particle diameter of the low-melting-point metal particles is 10 μm or less, the volume ratio of the low-melting-point metal particles to the thermal conductive particles can be reduced, and high thermal conductivity and low thermal resistance of the thermal conductive layer can be achieved. The volume average particle size of the low-melting point metal particles can be measured in the same manner as the volume average particle size of the thermally conductive particles.

[0057] The thermally conductive particles have a volume average particle size larger than that of the low-melting metal particles, and the volume average particle size ratio (α / β) between the thermally conductive particles α and the low-melting metal particles β is preferably 1.5 or more. The upper limit of the volume average particle size ratio (α / β) is preferably 10 or less. By using low-melting point metal particles having a smaller volume average particle size than the thermally conductive particles, the thermally conductive particles become the main component in the thermally conductive composition, and the low-melting point metal particles present between the thermally conductive particles melt when heated and alloy with the thermally conductive particles to form a network, thereby achieving high thermal conductivity and low thermal resistance.

[0058] In the thermally conductive composition for forming the thermally conductive layer, the volume ratio (α / β) of the thermally conductive particles α to the low-melting point metal particles β is preferably at least 1, and more preferably at least 1.5. The upper limit of the volume ratio (α / β) is preferably at most 4, and more preferably at most 3.

[0059] <Specific polymer> The thermally conductive composition preferably contains a specific polymer in order to impart flexibility and sheetability. As the specific polymer, a polymer having at least one structure selected from a phenoxy structure, a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, a polyamide structure, and a polycarbonate structure in the molecule is used.

[0060] Examples of the specific polymer include a phenoxy structure such as bisphenol A type and bisphenol F type, a polybutadiene structure such as polybutadiene and hydrogenated polybutadiene, a polysiloxane structure such as silicone rubber, a poly(meth)acrylate structure, a polyalkylene structure (preferably a polyalkylene structure having 2 to 15 carbon atoms, more preferably a polyalkylene structure having 3 to 10 carbon atoms, and even more preferably a polyalkylene structure having 5 to 6 carbon atoms), a polyalkyleneoxy structure (preferably a polyalkyleneoxy structure having 2 to 15 carbon atoms, more preferably a polyalkyleneoxy structure having 3 to 10 carbon atoms), and It is preferable that the polyalkyleneoxy structure has at least one structure selected from the group consisting of a polyalkyleneoxy structure having 5 to 6 carbon atoms, and more preferable that the polyalkyleneoxy structure has at least one structure selected from the group consisting of a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure, it is preferable that the polyalkyleneoxy structure has at least one structure selected from the group consisting of a phenoxy structure, a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure, and it is more preferable that the polyalkyleneoxy structure has at least one structure selected from the group consisting of a phenoxy structure, a polybutadiene structure, a polyisoprene structure, and a polycarbonate structure.

[0061] The specific polymer preferably has a high molecular weight in order to exhibit flexibility. The number average molecular weight (Mn) of the specific polymer is preferably 1,000 or more and 1,000,000 or less, and more preferably 5,000 or more and 900,000 or less. The number average molecular weight (Mn) is a polystyrene-equivalent number average molecular weight measured using GPC (gel permeation chromatography).

[0062] The specific polymer is preferably selected from polymers having a glass transition temperature (Tg) of 25°C or lower and polymers that are liquid at 25°C in order to exhibit flexibility. The glass transition temperature (Tg) of the polymer having a glass transition temperature of 25° C. or lower is preferably 20° C. or lower, more preferably 15° C. or lower. There is no particular restriction on the lower limit of the glass transition temperature, and it can be appropriately selected depending on the purpose, but it is preferably −15° C. or higher. As the polymer that is liquid at 25°C, a polymer that is liquid at 20°C or less is preferable, and a polymer that is liquid at 15°C or less is more preferable.

[0063] From the viewpoint of improving the mechanical strength of the cured product, the specific polymer preferably has a functional group capable of reacting with the curing component. The functional group capable of reacting with the curing component also includes a functional group that appears upon heating. The functional group capable of reacting with the curing component is, for example, one or more functional groups selected from the group consisting of a hydroxy group, a carboxy group, an acid anhydride group, a phenolic hydroxyl group, an epoxy group, an isocyanate group, and a urethane group. Among these, the functional group is preferably a hydroxy group, an acid anhydride group, a phenolic hydroxyl group, an epoxy group, an isocyanate group, or a urethane group, and more preferably a hydroxy group, an acid anhydride group, a phenolic hydroxyl group, or an epoxy group.

[0064] The content of the specific polymer is preferably from 1 vol% to 50 vol%, more preferably from 1 vol% to 30 vol%, and even more preferably from 1 vol% to 20 vol%, based on the total amount of the thermally conductive composition.

[0065] The average thickness of the heat conductive layer is not particularly limited and may be appropriately selected depending on the purpose, but is preferably from 20 μm to 300 μm, and more preferably from 50 μm to 200 μm.

[0066] <Facing substrate> The opposing substrate is disposed opposite the substrate, and its shape, structure, size, material, etc. are not particularly limited and can be appropriately selected depending on the purpose. The shape of the opposing substrate may be, for example, a plate shape, a sheet shape, etc. The structure of the opposing substrate may be, for example, a single-layer structure, a laminated structure, etc. The size of the opposing substrate may be appropriately selected depending on the application, etc. The material of the facing base material is a material that is easily wetted by solder, and includes at least one selected from copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof. The average thickness of the opposing substrate is not particularly limited and can be appropriately selected depending on the purpose. The opposing base material may be the heat spreader itself in the heat dissipation structure.

[0067] <Other materials> The other members are not particularly limited and can be appropriately selected depending on the purpose. For example, a protective layer can be mentioned.

[0068] (Method of manufacturing laminate) The method for producing a laminate of the present invention includes a metal layer forming step, a thermally conductive composition applying step, and a heating step, and may further include other steps as necessary. This makes it possible to manufacture a laminate that can reduce the contact resistance with the silicon substrate and achieve excellent thermal conductivity, adhesion, and reflow resistance, and thus makes it possible to suitably manufacture the laminate of this embodiment.

[0069] <Metal layer formation process> The metal layer forming step is a step of forming a metal layer having a seed layer containing at least one of Ti, W, Al, Mo, and Cr on a silicon substrate. The metal layer comprises at least a seed layer, and preferably further comprises a barrier layer, and preferably further comprises a top layer. The seed layer, barrier layer, and top layer may be appropriately selected from those described in the laminate of this embodiment.

[0070] The method for forming the metal layer on the silicon substrate is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include physical vapor deposition methods (PVD method, physical vapor deposition method) such as sputtering method, vacuum deposition method, ion plating method, etc.; chemical vapor deposition methods (CVD method) such as thermal chemical vapor deposition method (thermal CVD method), plasma CVD method, atomic layer deposition method (ALD method), etc. Among these, sputtering method is preferable.

[0071] -Silicon substrate- The silicon substrate can be appropriately selected from the items explained in the above-mentioned laminate of the present invention.

[0072] <Thermal conductive composition application step> The thermally conductive composition applying step is a step of applying a thermally conductive composition onto the metal layer.

[0073] Examples of methods for applying the thermally conductive composition onto the metal layer include spin coating, inkjet coating, blade coating, gravure coating, gravure offset coating, bar coating, roll coating, knife coating, air knife coating, comma coating, U comma coating, AKKU coating, smoothing coating, microgravure coating, reverse roll coating, four-roll coating, five-roll coating, dip coating, curtain coating, slide coating, and die coating. The thermally conductive composition in a sheet form may be applied onto the substrate by means of transfer or the like.

[0074] -Thermal conductive composition- The thermally conductive composition contains a curing component, a curing agent, thermally conductive particles, and low-melting point metal particles, and preferably contains a specific polymer, and further contains other components as necessary. The curing component, curing agent, thermally conductive particles, and low-melting point metal particles can be appropriately selected from those described above in the method for producing a laminate of the present invention.

[0075] The content of the curing component is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.5% by volume or more and 60% by volume or less based on the total amount of the thermally conductive composition.

[0076] The content of the curing agent is not particularly limited and can be appropriately selected depending on the purpose, but is preferably from 0.1 vol.% to 30 vol.%, more preferably from 0.5 vol.% to 20 vol.%, and even more preferably from 1 vol.% to 15 vol.%, based on the total amount of the thermally conductive composition.

[0077] <Heating process> The heating step is a step of heating the applied thermally conductive composition, thereby forming a thermally conductive layer on the metal layer.

[0078] The heating conditions are not particularly limited as long as the curing component and the curing agent contained in the thermally conductive composition react with each other to cure, and can be appropriately selected depending on the purpose. For example, the heating conditions are preferably 120°C to 190°C for 1 minute to 30 minutes, and more preferably 140°C to 170°C for 1 minute to 10 minutes.

[0079] By applying a thermally conductive composition onto the metal layer and then carrying out a heating step, the adhesion of the metal layer and the resulting thermally conductive layer can be improved. In addition, the flux activity of the curing agent is expressed in the heating step, and the wettability between the molten low-melting point metal and the thermally conductive particles can be improved.

[0080] <Other processes> The other steps are not particularly limited and may be appropriately selected depending on the purpose. For example, a protective layer forming step, an opposing substrate laminating step, and the like may be included.

[0081] Here, the laminate manufacturing method and the laminate according to the present invention will be described in detail with reference to the drawings. In each drawing, the same components are denoted by the same reference numerals, and duplicated descriptions may be omitted. In addition, the number, position, shape, etc. of the following components are not limited to the present embodiment, and may be any number, position, shape, etc. that is preferable for implementing the present invention.

[0082] FIG. 1 is a schematic diagram showing an example of a process for producing a laminate according to this embodiment. The pre-cured laminate 10a shown in FIG. 1 is a pre-cured laminate after the metal layer forming step and the thermally conductive composition applying step and before the heating step, and specifically has a metal layer 12 on a silicon substrate 11, a thermally conductive composition 14a containing thermally conductive particles 14b and low-melting point metal particles 14c on the metal layer 12, and an opposing substrate 15 on the thermally conductive composition 14a.

[0083] FIG. 2 is a schematic diagram showing an example of a laminate according to this embodiment. The laminate 10 shown in FIG. 2 has a metal layer 12 on a silicon substrate 11, a thermally conductive layer 14 containing thermally conductive particles 14b and a low-melting point metal 14d on the metal layer 12, and an opposing substrate 15 on the thermally conductive layer 14.

[0084] 3 to 5 are schematic diagrams showing other examples of the laminate according to this embodiment. Specifically, the metal layer 12 in the laminate 10 in FIG. 2 is shown in a variation, and the metal layer 12 may be a form consisting of a seed layer 12a (see FIG. 3), a form of a laminate in which the seed layer 12a and the barrier layer 12b are laminated in order from the silicon substrate 11 side (see FIG. 4), a form of a laminate in which the seed layer 12a, the barrier layer 12b, and the top layer 12c are laminated in order from the silicon substrate 11 side (see FIG. 5), or a form of a laminate in which the seed layer 12a and the top layer 12c are laminated in order from the silicon substrate 11 side (not shown). Any of the forms can be appropriately selected according to the purpose.

[0085] The laminate of the present invention can be suitably used, for example, as a thermal interface material (TIM) that fills the minute gap between a heat source such as an LSI and a heat sink, thereby allowing heat to flow smoothly between the two, or when adhering a heat dissipation substrate mounting an LED chip or an IC chip to a heat sink to form a power LED module or a power IC module. Here, the power LED module is classified into a wire bonding mounting type and a flip chip mounting type, and the power IC module is classified into a wire bonding mounting type.

[0086] (heat dissipation structure) The heat dissipation structure of the present embodiment includes a heat generating body, the above-described laminate of the present invention, and a heat dissipation member, and further includes other members as necessary.

[0087] The heating element is not particularly limited and can be appropriately selected depending on the purpose. Examples of the heating element include electronic components such as a central processing unit (CPU), a micro processing unit (MPU), and a graphics processing unit (GPU).

[0088] The heat dissipation member is not particularly limited as long as it is a structure that dissipates heat generated by an electronic component (heat generating element), and can be appropriately selected depending on the purpose. Examples of the heat dissipation member include a heat spreader, a heat sink, a vapor chamber, and a heat pipe. The heat spreader is a member for efficiently transferring heat from the electronic component to other components. The material of the heat spreader is not particularly limited and can be appropriately selected depending on the purpose, and examples of the material include copper and aluminum. The heat spreader is usually in a flat plate shape. The heat sink is a member for releasing heat from the electronic component into the air. The material of the heat sink is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include copper and aluminum. The heat sink has, for example, a plurality of fins. The heat sink has, for example, a base portion and a plurality of fins provided so as to extend in a non-parallel direction (for example, a direction perpendicular to) one surface of the base portion. The heat spreader and the heat sink are generally solid structures with no internal voids. The vapor chamber is a hollow structure. A volatile liquid is sealed in the internal space of the hollow structure. Examples of the vapor chamber include a hollow structure of the heat spreader, a hollow plate-shaped structure of the heat sink, and the like. The heat pipe is a hollow structure having a cylindrical, approximately cylindrical, or flattened tubular shape, and a volatile liquid is sealed in the internal space of the hollow structure.

[0089] Here, Fig. 6 is a schematic cross-sectional view showing an example of a semiconductor device as a heat dissipation structure. The laminate 7 of the present invention dissipates heat generated by an electronic component 3 such as a semiconductor element, and is fixed to a main surface 2a of the heat spreader 2 facing the electronic component 3, as shown in Fig. 4, and is sandwiched between the electronic component 3 and the heat spreader 2. In addition, the thermally conductive sheet 1 is sandwiched between the heat spreader 2 and a heat sink 5.

[0090] The heat spreader 2 is formed, for example, in a rectangular plate shape, and has a main surface 2a facing the electronic component 3 and a side wall 2b erected along the outer periphery of the main surface 2a. The heat spreader 2 has a thermally conductive sheet 1 provided on the main surface 2a surrounded by the side wall 2b, and a heat sink 5 provided on the other surface 2c opposite the main surface 2a via the thermally conductive sheet 1. The higher the thermal conductivity of the heat spreader 2, the lower the thermal resistance and the more efficiently the heat is absorbed from the electronic component 3 such as a semiconductor element, so that the heat spreader 2 can be formed, for example, using copper or aluminum, which have good thermal conductivity.

[0091] The electronic component 3 is, for example, a semiconductor element such as a BGA, and is mounted on the wiring board 6. The tip surface of the side wall 2b of the heat spreader 2 is also mounted on the wiring board 6, so that the side wall 2b surrounds the electronic component 3 at a predetermined distance. By providing the laminate 7 of the present invention on the main surface 2a of the heat spreader 2, a heat dissipation member that absorbs heat generated by the electronic component 3 and dissipates the heat from the heat sink 5 is formed. EXAMPLES

[0092] Examples of the present invention will be described below, but the present invention is not limited to these examples.

[0093] Example 1 <Preparation of Thermally Conductive Composition> The compositions and contents shown in Table 1 were mixed uniformly using a stirring device (Awatori Rentaro Automatic Orbital Mixer, manufactured by Thinky Corporation) to prepare thermally conductive compositions. The content of each component in Table 1 is in volume percent.

[0094] <Formation of metal layer> On a substrate (silicon substrate) measuring 20 mm × 20 mm × 0.725 mm, Ti, Ni, and Au were sequentially laminated by a sputtering method so that, from the silicon substrate side, the seed layer (Ti), barrier layer (Ni), and top layer (Au) were 100 nm, 200 nm, and 200 nm, respectively, to obtain a silicon substrate provided with a metal layer having a Ti / Ni / Au laminate structure. The sputtering method was performed using a sputtering device (SPC-530H, manufactured by Canon Anelva Corporation) under the conditions of argon gas at 100 sccm (0.52 Pa), silicon substrate temperature: 24°C (RT), and pressure: 1.8 × 10 -3 The experiment was carried out under the conditions of 100 Pa and voltage: DC 500 W. Table 1 shows the metal types of the seed layer, barrier layer, and top layer of the metal layer, and the average thickness [μm] of each layer.

[0095] <Formation of thermally conductive layer and production of laminate> Next, a thermally conductive composition was applied onto the metal layer so that the average thickness after curing would be 100 μm, and a 20 mm × 20 mm × 1 mm opposing substrate (copper) was laminated onto the thermally conductive composition. The composition was then heated in two stages, at 150°C for 5 minutes and at 170°C for 60 minutes, and cured to form a thermally conductive layer, thereby producing the laminate of Example 1.

[0096] Example 2 A laminate of Example 2 was produced in the same manner as in Example 1, except that the barrier layer in the metal layer was changed from nickel (Ni) to niobium (Nb).

[0097] Example 3 A laminate of Example 2 was produced in the same manner as in Example 1, except that the top layer of the metal layer was changed from gold (Au) to silver (Ag).

[0098] Example 4 A laminate of Example 4 was produced in the same manner as in Example 1, except that the seed layer in the metal layer was changed from titanium (Ti) to tungsten (W).

[0099] Example 5 A laminate of Example 5 was produced in the same manner as in Example 1, except that the top layer of the metal layer in Example 1 was not formed.

[0100] Example 6 A laminate of Example 6 was produced in the same manner as in Example 1, except that the thickness of the top layer in the metal layer was changed from 200 nm to 700 nm.

[0101] Comparative Example 1 A laminate of Comparative Example 1 was produced in the same manner as in Example 1, except that, instead of forming a metal layer, a thermally conductive layer was formed directly on the silicon substrate.

[0102] Comparative Example 2 In Example 1, instead of the thermally conductive layer, a commercially available solder sheet (In 52 Sn 48 A tin foil lead-free solder sheet (100 mm × 50 mm × 0.10 mm, manufactured by Sanyinghe Official Store) was used to laminate the cut-out solder sheet onto the metal layer, and a 20 mm × 20 mm × 1 mm opposing substrate (copper) was laminated on top of this. The substrate was then heated and melted at 160°C for 5 minutes to form a thermally conductive layer, thereby producing a laminate for Comparative Example 2.

[0103] Comparative Example 3 In Example 1, a commercially available indium sheet (4N-In sheet, 100 mm x 100 mm x 0.10 mm, manufactured by Nippon Invest Co., Ltd.) cut to a size of 20 mm x 20 mm was used instead of the thermally conductive layer, and the cut-out indium sheet was laminated on the metal layer. A 20 mm x 20 mm x 1 mm opposing substrate (copper) was laminated on top of this, and the thermally conductive layer was formed by heating and melting at 160°C for 5 minutes, thereby producing the laminate of Comparative Example 3.

[0104] Next, for each of the obtained laminates, "measurement of the average thickness of each layer," "thermal conductivity," "adhesiveness," and "reflow resistance" were evaluated as follows. The results are shown in Tables 1 and 2.

[0105] <Measurement of the average thickness of each layer> Each laminate was cut, the cut surface was polished, and the polished surface was photographed with a scanning electron microscope (S-3000N, manufactured by Hitachi, Ltd.). The thickness of each layer was measured from the cut surface of the laminate, and the average thickness was calculated at three arbitrary points. The results are shown in Tables 1 and 2. It was confirmed that the laminates of Examples 1 to 6 had a metal layer 12, a thermally conductive layer 14, and an opposing substrate 15 in this order on a silicon substrate 11, corresponding to the cross-sectional view of the laminate shown in Figure 2.

[0106] <Thermal conductivity> <<Preparation of laminated body after compression>> Each laminate was sandwiched between a 20 mm x 20 mm square silicon plate (thickness 0.77 mm) and a 20 mm diameter copper plate (thickness 1.0 mm) and pressed for 5 minutes using a mini press under the following conditions: upper plate temperature on the copper substrate side was 150°C, lower plate temperature on the silicon substrate side was 150°C, and set air pressure was 0.11 MPa (40 psi in terms of pressure).

[0107] <<Evaluation of thermal conductivity>> After bonding, the thermal resistance (℃ cm) of the laminate (interface Cu and silicon) was measured using a method in accordance with ASTM-D5470. 2 The thermal resistance of the laminate was calculated by subtracting the thermal resistance of the substrate (silicon substrate) and the opposing substrate (copper substrate) from the results, and the thermal resistance of the portion excluding the substrate and the opposing substrate from the laminate was calculated. The thermal conductivity (W / m K) was calculated from this thermal resistance and the thickness (100 μm) of the portion excluding the substrate and the opposing substrate from the laminate, and the thermal conductivity was evaluated according to the following criteria. [Evaluation Criteria] ◎: Thermal conductivity is 20 W / m K or higher. Good: Thermal conductivity is 10 W / m K or more and less than 20 W / m K. ×: Thermal conductivity is less than 10 W / m K.

[0108] <Adhesiveness> For each example, the adhesiveness of the laminate after compression bonding was evaluated according to the following procedure. The laminate after compression bonding was prepared according to the procedure explained in the above section on <Thermal Conductivity>. As a reliability test, a bond tester (4000Plus, manufactured by Nordson DAGE) was used to perform a shear test on the laminate after compression bonding under the test conditions of a shear rate of 200 μm, height of 150 μm, n=3, and an environment of 130°C, and the adhesion at high temperatures was evaluated. [Evaluation Criteria] ◯: The adhesive strength is 3 kg or more. ×: The adhesive strength is less than 3 kg.

[0109] <Reflow resistance> <<Preparation of laminate after reflow>> The laminate after compression bonding was subjected to a treatment simulating reflow conditions, in which the laminate was heated at 260°C for 5 minutes, to remelt (reflow) the low-melting point metal particles of each laminate, thereby obtaining a reflowed laminate.

[0110] <<Evaluation of thermal conductivity after reflow>> After reflow, the laminate (interface Cu and silicon) was measured for thermal resistance (℃ cm 2 The thermal resistance of the laminate excluding the substrate and the opposing substrate was calculated by subtracting the thermal resistance of the substrate (silicon substrate) and the opposing substrate (copper substrate) from the results, and the thermal conductivity (W / m K) was calculated from this thermal resistance and the thickness (100 μm) of the laminate excluding the substrate and the opposing substrate, and the reflow resistance (thermal conductivity after reflow) was evaluated according to the following criteria. [Evaluation Criteria] ◎: Thermal conductivity is 20 W / m K or higher. Good: Thermal conductivity is 12 W / m K or more and less than 20 W / m K. ×: Thermal conductivity is less than 12 W / m K.

[0111] [Table 1]

[0112] [Table 2]

[0113] Details of each component in Table 1 are as follows.

[0114] -Curing component- Curing component (oxetane compound): ETERNACOLL (registered trademark) OXBP (manufactured by Ube Industries, Ltd.), 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl

[0115] - Hardener - Curing agent: a polyfunctional carboxylic acid represented by the general formula (I) (pentanedioic acid-1,1',1''-(1,2,3-propanetriyl) ester; molecular formula: C 18 H 26 O 12 ;Dexerials Corporation synthetic product)

[0116] -Low melting point metal particles (solder particles)- Sn 42 Bi 58 Manufactured by Mitsui Mining & Smelting Co., Ltd., Volume average particle size Dv: 6μm, Melting point 139℃ The volume average particle size Dv of the low-melting point metal particles is a value measured by a laser diffraction / scattering type particle size distribution measuring device (product name: Microtrac MT3300EXII).

[0117] -Thermal conductive particles- Ag-coated Cu particles (D50: 10 μm): Ag-coated Cu particles, manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size Dv: 10 μm The volume average particle size Dv of the thermally conductive particles is a value measured by a laser diffraction / scattering type particle size distribution measuring device (product name: Microtrac MT3300EXII).

[0118] -Thermoplastic resin- YP-50 (manufactured by Nippon Steel Chemical & Material Co., Ltd.), a polyhydroxypolyether synthesized from bisphenols and epichlorohydrin [Industrial Applicability]

[0119] The laminate of the present invention can achieve excellent heat resistance, thermal conductivity, and adhesion as a thermal interface material (TIM), and is therefore suitable for use in, for example, the vicinity of various electric devices such as CPUs, MPUs, power transistors, LEDs, and laser diodes, whose element operation efficiency, life span, and the like are adversely affected by temperature. [Explanation of symbols]

[0120] 1. Thermally conductive sheet 2 Heat spreader 2a Main surface 3 Heating elements (electronic components) 3a Top side 5. Heat sink 6 Wiring board 7 Laminate 10 Laminate 10a Laminate before curing 11 Silicon substrate 12 metal layer 12a Seed layer 12b Barrier layer 12c Top Tier 14 Thermal Conductive Layer 14a Thermally conductive composition 14b Thermally conductive particles 14c Low melting point metal particles 14d Low melting point metals 15 Opposing substrate

Claims

1. A silicon substrate; a metal layer provided on the silicon substrate; a heat conductive layer provided on the metal layer, the heat conductive layer including a hardening component, a hardening agent, heat conductive particles, and a low melting point metal; 13. A laminate, wherein the metal layer has a seed layer containing at least one of Ti, W, Al, Mo, and Cr.

2. 2. The laminate according to claim 1, wherein the metal layer has, in order from the silicon substrate side, the seed layer and a barrier layer containing at least one of Ni, Al, Mo, Nb, TiN, TaN, and WN.

3. The laminate according to claim 2 , wherein the metal layer includes, in order from the silicon substrate side, the seed layer, the barrier layer, and a top layer containing at least one of Ag, Au, Cu, Pd, and Pt.

4. 4. The laminate according to claim 1, having a thermal conductivity of 30 W / (m·K) or more.

5. forming a metal layer having a seed layer containing at least one of Ti, W, Al, Mo, and Cr on a silicon substrate; applying a thermally conductive composition onto the metal layer, the thermally conductive composition including a curing component, a curing agent, thermally conductive particles, and low melting point metal particles; and heating the applied thermally conductive composition.

6. 6. The method for producing a laminate according to claim 5, wherein the metal layer has, in order from the silicon substrate side, the seed layer and a barrier layer containing at least one of Ni, Al, Mo, Nb, TiN, TaN, and WN.

7. The method for producing a laminate according to claim 6, wherein the metal layer has, in order from the silicon substrate side, the seed layer, the barrier layer, and a top layer containing at least one of Ag, Au, Cu, Pd, and Pt.

8. The method for producing a laminate according to any one of claims 5 to 7, wherein the metal layer is formed by sputtering.